A Compact Coupled-Fed Loop Antenna for Mobile LTE Smartphones. (11th March 2018) - Wang, Ping; Shao, Yu; Huang, Dong; Basit, Muhammad Abdul
Abstract : A coupled-fed loop antenna with Octa-bands operation for long-term evolution (LTE) smartphones is proposed in this paper. The antenna occupies a nonground space of only 6.5 mm × 72 mm, and two wide-band operations can be achieved by exploiting the multimode characteristics of loop antenna and using high-pass matching circuits. In low band, the LTE700/GSM850/900 operation is achieved by the loop mode of 0.5 λ and matching chip capacitor which generates a dual-resonance mode at 0.74 GHz and 0.9 GHz. In high band, the 1 λ mode, the 1.5 λ mode, and the 2 λ mode of the entire loop are combined with the 0.5 λ mode of the left-side coupling loop to cover the DCS1800/PCS1900/UMTS 2100/LTE 2300/2500 operation bands. The measured average realized gains and efficiencies are approximately 1.56 dBi/2.38 dBi and 55.3%/63.6% in the two bands, and a good radiation pattern is achieved as well.